Antibody-drug conjugates targeting the cadherin, claudin and nectin families of adhesion molecules - Katoh, Masuko; Loriot, Yohann; Nakayama, Izuma; Hamada, Akinobu; Shitara, Kohei; Katoh, Masaru (Frontiers in Molecular Medicine, 2025)
The classical cadherin (CDH), claudin (CLDN) and nectin families of transmembrane-type adhesion molecules are located at adherens or tight junctions in epithelial cells but diffuse to the nonjunctional cell surface in solid tumors with epithelial–mesenchymal plasticity. Human/humanized antibody-drug conjugates (ADCs) with chemical linkers and cytotoxic payloads have been developed for the treatment of malignancies. Here, the clinical development of ADCs that target CDH6, CDH17, CLDN6, CLDN18.2 and NECTIN4 is reviewed. Enfortumab vedotin is an NECTIN4-targeting antibody-drug conjugate that is approved for the treatment of urothelial cancer, whereas other ADCs or derivatives that target NECTIN4, such as bulumtatug fuvedotin, SHR-A2102 and zelenectide pevedotin, are being studied in randomized phase III clinical trials. In contrast, arcotatug tavatecan, garetatug rezetecan, sonesitatug vedotin and tecotabart vedotin are anti-CLDN18.2 ADCs in phase III clinical trials for the treatment of CLDN18.2-positive gastric or gastroesophageal junction adenocarcinomas, and raludotatug deruxtecan is an anti-CDH6 ADC in a phase II/III clinical trial for the treatment of platinum-resistant ovarian cancer. ADCs that target cell-cell adhesion molecules are a rapidly emerging class of cancer therapeutics, and bispecific ADCs and longitudinal companion diagnostics are emerging to further improve the clinical benefits of conventional ADCs.